Analyzing the influence of large-scale weather patterns on renewable energy systems: A review - Kira Layer; Stephanie Gutmayer; Thorben Sandmeier; Jonas Ringger; Jan Cermak; Wolf Fichtner (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2026)
Electricity generation as well as electricity demand are dependent on the weather and climate, and this dependency is expected to further increase in the future. Challenges in energy systems arising from this dependency can be studied using large-scale weather patterns (WPs). These WPs can help reveal the atmospheric drivers of the challenges, but there exist many different classifications of large-scale WPs. Although WPs are widely used in energy-related studies, to our knowledge, no systematic review has yet evaluated the applicability of weather pattern classifications to analyzing extreme events and variability in energy systems. In this study, we aim to fill this gap by reviewing and combining literature dealing with both WP classifications and weather-induced challenges in energy systems. A total of 69 studies are included, which use different classification methods to study weather-induced challenges on energy systems. Overall, most challenges to the energy system arise during blocking weather patterns. Furthermore, we find that stable large-scale WPs allow for better forecasts of wind power generation if combined with other predictors. This review reveals research gaps underscoring the need to consider the whole energy system, including demand and the electricity grid, not only the generation of wind power and photovoltaics.
Keywords: 330; weather patterns; weather regimes; high residual load events; energy drought; weather variability; forecasting; energy system